2021
DOI: 10.3390/vaccines9030226
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of a COVID-19 Vaccine among the Saudi Population

Abstract: To investigate the associated factors underlying vaccination intentions for Coronavirus Disease 2019 (COVID-19), an online cross-sectional survey was conducted among adults 18 years or over in the Kingdom of Saudi Arabia. Data were collected between 8 and 14 December 2020. A logistic regression analysis was employed to examine and identify the variables associated with vaccination intentions for COVID-19, with the odds ratio (OR) and 95% confidence interval (CI) also calculated. A total of 2137 respondents com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
104
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(142 citation statements)
references
References 28 publications
17
104
6
Order By: Relevance
“… 21 Yoda & Katsuyama 60 2021 1100 Residents CS Japan 65.7% Age (≥70 years), residency (rural), having underlying medical conditions, and gender (male). 22 Zigron et al 62 2021 506 Dentists, dental residents, and oral medicine specialists CS Israel 85% Occupation (unemployment) 23 Abedin et al 63 2021 3646 Adults (≥18 years) CS Bangladesh 74.6% NA 24 Alfageeh et al 50 2021 2137 Adults (≥18 years) CS Saudi Arabia 48% Receiving the seasonal influenza vaccination in the past, believed in mandatory COVID-19 vaccination, and reported high levels of concern about contracting COVID-19. 25 Al-Mohaithef et al 51 2021 658 Adults (≥18 years) CS Saudi Arabia 53.3% High-risk perception, and higher trust in the healthcare system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 21 Yoda & Katsuyama 60 2021 1100 Residents CS Japan 65.7% Age (≥70 years), residency (rural), having underlying medical conditions, and gender (male). 22 Zigron et al 62 2021 506 Dentists, dental residents, and oral medicine specialists CS Israel 85% Occupation (unemployment) 23 Abedin et al 63 2021 3646 Adults (≥18 years) CS Bangladesh 74.6% NA 24 Alfageeh et al 50 2021 2137 Adults (≥18 years) CS Saudi Arabia 48% Receiving the seasonal influenza vaccination in the past, believed in mandatory COVID-19 vaccination, and reported high levels of concern about contracting COVID-19. 25 Al-Mohaithef et al 51 2021 658 Adults (≥18 years) CS Saudi Arabia 53.3% High-risk perception, and higher trust in the healthcare system.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the study reported that factors such as perceived risk of COVID-19, 30 , 31 , 34 , 44 , 47 , 50 , 51 , 53 , 58 , 59 , 68–71 trust in healthcare system, 46 , 51 health insurance, 31 , 48 norms, 31 , 65 attitude towards a vaccine, 31 , 55 , 58 perceived benefit of vaccine, 31 , 40 , 46 , 65 , 70 perceived vaccine barriers, 31 , 40 , 70 self-efficacy, 31 up-to-date on vaccinations, 32 being tested for COVID-19 in the past, 32 , 72 responsibility, 39 perceived efficacy of the COVID-19 vaccination, 41 , 47 use of social media for COVID-19 vaccine-related information, 41 recommended for vaccination, 34 political leaning, 34 perceived severity of COVID-19, 34 , 44 , 46 , 70 , 74 perceived effectiveness of a COVID-19 vaccine, 34 , 43 , 59 , 61 belief that vaccination makes them feel less worried about COVID-19, 59 believing in mandatory COVID-19 vaccination, 50 perceived potential vaccine harms, 34 , 42 , 53 , 58 presence of chronic disease, 45 , 48 , 60 previously received an influenza vaccine, 43 , 45 , 47 <...>…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the availability of the vaccine for the population in Saudi Arabia, there is a variation in people’s acceptance to take the vaccine and this is probably due to the fact that these vaccines were developed in a short time compared to the previously approved vaccines which usually take years before approval. Another reason for this variation could be related to the usage of a newly emerging technique for some of the COVID-19 vaccines, mRNA vaccines [ 12 , 13 , 14 , 15 , 16 ]. These two major factors may raise the concern among some individuals about potential severe post-vaccination side effects, although several reports describing the expected side effects have been issued recently [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Education of the public will be crucial to maximise uptake of vaccines against COVID-19. This includes healthcare professionals: a recent survey from Saudi Arabia found that half of a population of 763 “healthcare workers” (otherwise undefined) would not accept vaccination as soon as a vaccine became available [ 64 ], a proportion almost identical to that from the general population [ 65 ]. Perceived concerns over the level of demonstration of safety for the vaccines were important here.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%